Renal Farnesoid X Receptor improves high fructose-induced salt-sensitive hypertension in mice by inhibiting DNM3 to promote nitro oxide production. Issue 8 (5th August 2022) - Zhu, Yeyan; Tao, Yufeng; Wu, Chunying; Zeng, Yuting; Du, Huiting; Xiang, Qunkun; Chen, Yang; Zhu, Qing; Wang, Lei
Abstract : Objective: Farnesoid X Receptor (FXR) is highly expressed in renal tubules, activation of which attenuates renal injury by suppressing inflammation and fibrosis. However, whether renal FXR contributes to the regulation of blood pressure (BP) is poorly understood. This study aimed to investigate the anti-hypertensive effect of renal FXR on high-fructose-induced salt-sensitive hypertension and underlying mechanism. Methods: Hypertension was induced in male C57BL/6 mice by 20% fructose in drinking water with 4% sodium chloride in diet (HFS) for 8 weeks. The effects of FXR on NO production were estimated in vitro and in vivo . Results: Compared with control, HFS intake elevated BP, enhanced renal injury and reduced renal NO levels as well as FXR expression in the kidney of mice. In the mouse renal collecting duct cells mIMCD-K2, FXR agonists promoted NO production by enhancing the expression of neuronal nitric oxide synthase (nNOS) and inducible nitric oxide synthase (iNOS), whereas this effect was diminished by fxr knockdown. We further found that Dynamin 3 (DNM3), a binding protein with nNOS in the renal medulla, was inhibited by FXR and its deficiency elevated NO production in mIMCD-K2 cells. In HFS-fed mice, renal fxr overexpression significantly attenuated hypertension and renal fibrosis, regulated the expression of DNM3/nNOS/iNOS, and increased renal NO levels. Conclusion: Our results demonstrated that renal FXR prevents HFS-induced hypertension by inhibiting DNM3 to promote NO production. These findings provide insights into the role and potential mechanism of renal FXR for the treatment of hypertension.